Альтернативные энергоносители в виде гидратов метана (клатратов) и сероводорода - Маляренко, Виталий Андреевич; Яковлев, Анатолий Иванович; Губин, С. В. (Національний технічний університет "Харківський політехнічний інститут", 2011)
Рассмотрены исследования газовых энергоносителей в виде газогидратов и сероводорода, расположенных в морской воде и на дне морей и океанов. Описаны их свойства, приведена количественная оценки по данным различных авторов.

The article considers the research of gas energy carriers in the form of gas-hydrates and hydrogen sulfide contained in the sea water and at the bottom of seas and oceans. Their properties are described and a quantitative evaluation according to the data of various authors is given.
Alternative energy carriers as hydrates of methane (clath-rates) and hydrogen sulphide
Keywords: энергетический кризис; энергетика; газовые факелы; запасы газа